NIV Cultural Backgrounds Study Bible : Bringing to Life the Ancient World of Scripture - Keener, Craig S., 1960-; Walton, John H., 1952- (Grand Rapids : Zondervan, 2016)
The Bible was originally written to an ancient people removed from us by thousands of years and thousands of miles. The Scriptures include subtle culturally based nuances, undertones, and referances to ancient events, literature, and customs that were intuitively understood by those who first heard the Scriptures read. The NIV Cultural Backgrounds Study Bible gives you a window into this word.
Includes index and concordance.
English.
Keywords: Bible -- Reference editions; Bible